Effect of hexavalent chromium-treated sperm on in vitro fertilization and embryo development. (September 2016) - Yoisungnern, Ton; Das, Joydeep; Choi, Yun-Jung; Parnpai, Rangsun; Kim, Jin-Hoi
Hexavalent chromium (Cr(VI)) is an environmental contaminant that is associated with reproductive abnormalities in both humans and animals. In the present study, we evaluated the cytotoxic effect of Cr(VI) on sperm function and subsequent embryo development after in vitro fertilization (IVF). Sperm obtained from BDF1 male mice were treated with potassium dichromate (0, 3.125, 6.25, 12.5, 25, or 50 μM) for 3 h. Cr(VI) significantly decreased sperm viability and acrosome reaction with increasing dose. These Cr(VI)-treated sperms were further used for IVF of oocytes obtained from BDF1 female mice. Results showed that Cr(VI)-treated sperm caused a significant reduction in IVF success, higher developmental arrest at the two-cell stage of embryos, and delayed blastocyst formation with increasing dose. In particular, most blastocysts from the Cr(VI)-treated sperm resulted in hatching failure as well as decreased inner cell mass and trophectoderm (TE). Furthermore, blastocysts obtained from Cr(VI)-treated sperm showed lower expression of not only TE-associated genes ( eomes, cdx2, and krt8 ) but also pluripotent marker genes ( sox2, pou5f1, and klf4 ) that are responsible for further embryo development of blastocyst embryos. The results of our current study showed that Cr(VI)-treated sperm had negative effects on oocyte fertilization and subsequent embryo development.